THE EFFECT OF CAREER DEVELOPMENT, JOB SATISFACTION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT CERAH SINERGI SEJAHTERA - agustian, wiwin; Esa, Gilang Anugrah; Mellita, Dina; Noviardi, Andrian (Jurnal Ecoment Global, 2025)
Abstract. Objective: This study aims to determine whether career development, job satisfaction and work motivation affect employee performance at PT. Cerah Sinergi Sejahtera. The type of quantitative research aims to determine the effect of career development, job satisfaction and work motivation as independent variables and employee performance as dependent variables. Design/Method/Approach: the method used in this study is a quantitative descriptive method with an analysis tool using multiple regression. The data used are primary data sourced from questionnaires with a sample of 54 respondents. Discussion: The results of the analysis using the t test show that career development does not affect employee performance at PT. Cerah Sinergi Sejahtera. Job satisfaction has a positive effect on employee performance at PT. Cerah Sinergi Sejahtera. Work motivation has a positive effect on employee performance at PT. Cerah Sinergi Sejahtera. The results of the determination coefficient test of the regression model show an R Square value of 0.828. This explains that 82.8% of career development variables, job satisfaction and work motivation have an effect on employee performance at PT. Cerah Sinergi Sejahtera and the remaining 19.8% is influenced by other variables outside of this study. Conclusion/suggestion: PT. Cerah Sinergi Sejahtera should prepare a structured career development program, including regular training, mentoring and fair promotion opportunities, this will be able to help employees to increase motivation so that employee job satisfaction can be achieved. Keywords: Career Development, Job Satisfaction, Work Motivation, Employee Performance